A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive. (1st March 2023) - Wei, Guang-Yi; Zhang, Feifei; Yin, Yi-Sheng; Lin, Yi-Bo; Pogge von Strandmann, Philip A.E.; Cao, Mengchun; Li, Na; Xiong, Guolin; Chen, Xinran; Fan, Caiwei; Xu, Changgui; Tan, Fei; et al.
Abstract: Lithium isotope (δ 7 Li) variations in marine carbonate sediments and rocks have been widely used to reconstruct global seawater Li isotope compositions and then trace the paleo-weathering processes. However, there are still debates on whether ancient carbonates can faithfully document original seawater δ 7 Li signals, as δ 7 Li values of shallow-water carbonates are tightly related to carbonate mineralogy and diagenetic alteration. In this study, we present high-resolution δ 7 Li, trace element and carbonate mineralogy data of shallow-water carbonate deposits from two shallow drillcores (Jiuzhang A and B) and a deep drillcore (XK-1) in the South China Sea. We compare these new δ 7 Li data to the ca. 13 Myr history of seawater δ 7 Li evolution from the middle Miocene to Pleistocene, in order to better constrain the effects of carbonate mineralogy and early diagenesis on δ 7 Li values of bulk inorganic carbonates. We observe that the δ 7 Li values of primary carbonate deposits in Jiuzhang A, B and the uppermost XK-1 drillcores (24.6% ± 1.6%, n = 37, 1σ) are significantly lower than modern seawater δ 7 Li values (Δ 7 Liprimary-seawater = ∼–6.0%). In contrast, marine diagenetic carbonates in the XK-1 drillcore exhibit δ 7 Li values of 28.7% ± 0.7% (n = 54, 1σ), approaching coeval seawater values (Δ 7 Limarine diagenetic-seawater = ∼–2.0%) and much higher than those of primary carbonate deposits. Meteoric diagenetic carbonates in the XK-1 drillcore show δ 7 Li values of 22.4% ± 1.6% (n = 46, 1σ), close to that of primary carbonate deposits in Jiuzhang A, B and the uppermost XK-1 drillcores, but significantly lower than coeval seawater δ 7 Li values (Δ 7 Limeteoric diagenetic-seawater = –5.0% to –9‰ for modern and Miocene seawater). Such δ 7 Li variations in shallow-water carbonates are attributed to variations in carbonate mineralogy (i.e., aragonite, high-Mg calcite and low-Mg calcite) and diagenetic regimes (fluid- or sediment-buffered conditions of marine and meteoric diagenesis). By comparing δ 7 Li data from the South China Sea to those from the Bahamas, we suggest strongly fluid-buffered conditions for Li isotopes during marine diagenesis, resulting in δ 7 Li values of marine limestones and dolostones approaching ambient seawater δ 7 Li signals. In contrast, meteoric diagenetic carbonates, likely marked by sediment-buffered conditions, may inherit the original δ 7 Li signals of primary carbonate deposits. Hence, full considerations of the carbonate mineralogy and diagenesis facilitate a better use of bulk inorganic carbonate-archived δ 7 Li to reconstruct paleo-weathering evolution in deep time lacking the skeletal fossil records.